ChemInform Abstract: Chemoselective Oxidative C(CO)—C(Methyl) Bond Cleavage of Methyl Ketones to Aldehydes Catalyzed by CuI with Molecular Oxygen. Issue 12 (25th March 2014) - Zhang, Lin; Bi, Xihe; Guan, Xiaoxue; Li, Xingqi; Liu, Qun; Barry, Badru‐Deen; Liao, Peiqiu
Abstract A wide range of aromatic methyl ketones as well as aliphatic methyl ketones are subjected to the copper‐catalyzed oxidative cleavage of the C(CO)‐C(CH3) bond to yield the corresponding aldehydes.The oxidation terminates at the aldehyde stage and can be considered as an unprecedented dehydrogenation of saturated aliphatics.